Actuarial neutrality and financial incentives for early retirement in the Austrian pension system - Michael Christl; Dénes Kucsera (DANUBE: Law, Economics and Social Issues Review, 2019)
This paper takes a closer look at the existing early retirement schemes in Austria and analyses whether early retirement imposes a financial burden on the pension system (actuarial neutrality). Additionally, we compute incentive-neutral deductions for early retirement. These deductions reflect the view of the individual, who faces option of retiring earlier or working another year. Incentive neutral deductions would imply that an individual is indifferent between both. Our results highlight substantial differences between both measures. While the current deduction rate of 5.1% in the Austrian age corridor is, on average, close to actuarial neutrality, it is lower than the incentive-neutral deductions. This indicates that there are financial incentives for early retirement, which may arise due to the Austrian tax system. Additionally, we show that both actuarial and incentive neutrality differ substantially across socio-economic characteristics, such as gender, wages and (early) retirement age.
Keywords: 330; Pension System; Actuarial Neutrality; Incentive Neutrality; Deductions; Early Retirement